1980
DOI: 10.1002/ana.410080411
|View full text |Cite
|
Sign up to set email alerts
|

Failure of intravenous and intrathecal cytarabine to modify central nervous system IgG synthesis in multiple sclerosis

Abstract: To study the nature of the multiple sclerosis (MS) central nervous system (CNS) immune reaction, cytarabine (ara-C) was administered intravenously to three patients and intrathecally to another seven. Although intravenous administration severely suppressed circulating leukocytes derived fom the bone marrow, there was no change in de novo CNS IgG synthesis (rate or presence of CSF IgG oligoclones). Therefore, the MS CNS immune reaction can persist in the presence of severe granulocytopenia and severe monocytope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The OCB pattern and IgG index were also unaffected in an SPMS patient who underwent two treatments of IT rituximab (Studer et al 2014). That IT antibody production is unaffected by such potent interventions as intracranial radiation (Tourtellotte et al 1980a), IT cytarabine (Tourtellotte et al 1980b), and autologous hematopoietic stem-cell transplantation (Saiz et al 2001;Nash et al 2003) is a testament to the difficulty of targeting the inflammatory process in the CNS and meninges.…”
Section: Progressive Multiple Sclerosismentioning
confidence: 99%
“…The OCB pattern and IgG index were also unaffected in an SPMS patient who underwent two treatments of IT rituximab (Studer et al 2014). That IT antibody production is unaffected by such potent interventions as intracranial radiation (Tourtellotte et al 1980a), IT cytarabine (Tourtellotte et al 1980b), and autologous hematopoietic stem-cell transplantation (Saiz et al 2001;Nash et al 2003) is a testament to the difficulty of targeting the inflammatory process in the CNS and meninges.…”
Section: Progressive Multiple Sclerosismentioning
confidence: 99%
“…Cytarabine (ara-C) is an antimetabolic agent interfering with DNA synthesis and is used in chemotherapeutic regimens for treating lymphomas. Cytotoxic levels administered in the systemic compartment do not achieve cytotoxic levels in the CSF, and reciprocally [ 93 ]. None of the 10 patients given cytarabine either systemically or intrathecally had changes in the number or pattern of CSF OCB.…”
Section: None Of the Available Ms Drugs Deplete Intrathecal Ig Synmentioning
confidence: 99%
“…CNS IgG synthesis slightly decreased (about 10%) after systemic infusion during the next month. However, CNS IgG synthesis transiently rose during the week following intrathecal administration, while at the same time CSF floating cells were low, and then all returned to their pretreatment level [ 93 ].…”
Section: None Of the Available Ms Drugs Deplete Intrathecal Ig Synmentioning
confidence: 99%
“…Silagi 33 has shown that RNA and protein synthesis were not affected in L cells exposed to lethal doses of Ara-C, and Ben-Porat et al 34 have demonstrated that Ara-C had no effect on the synthesis of pseudorabies virus structural proteins, or their movement from the cytoplasm to the nucleus, while it prevented the synthesis of viral DNA. Additionally, Tourtellotte et al 35 have shown that intravenous administration of Ara-C had no effect on de novo central nervous system immunoglobulin G synthesis in humans in spite of severe granulocytopenia and monocytopenia of 1 or 2 weeks' duration. In patients given the drug intrathecally, cytotoxic levels were maintained in the central nervous system for over 24 hours with no evidence of altered immunoglobulin synthesis or leukopenia.…”
Section: Figure 3 Effect Of Cytosine Arabinoside (Ara-c) Treatment Omentioning
confidence: 99%